Epistemologi Falsifikasionisme Popper dan Mitos Universalisme Barat: Menyoal Proyek Demokratisasi AS di Dunia Arab - Mas'odi, Mas'odi (International Conference on Islamic Studies, 2020)
This research tries to see and analyze how the democratization project - as a symbol of the universalism of Western civilization - has become a dogmatic political tool that has been instigated by the United States (US) in several countries in the Arab world. This research will also look critically at how the US democratization project in the Arab world becomes a barometer to test the absolutism of the discourse of Western universalism. This research uses qualitative research and is descriptive analytical in nature. In exploring the academic problems, this research uses the epistemological approach of Karl Raimund Popper's Falsificationism, as a step to test the resilience of the narrative of Western universalism from the falsification stage. The results of this research indicate that the US track record in fighting for the Arab nation's democratic rights is only an illusion. Democratic idealism was sacrificed on the basis of the US political economy profit calculation. This can be seen from the US track record in sustaining the oligarchic power of Arab rulers who tend to be authoritarian, such as Shah Pahlavi in ​​Iran, Hosni Mubarok in Egypt, Ben Ali in Tunisia, and Attaturk in Turkey. The US siding with Arab countries is also not based on the democratic government system adopted by the Arab countries. This can be seen from the US siding with Saudi Arabia and the UEA which adheres to a monarchy system on the one hand, and hostility towards Libya, Yemen, and Syria, on the other. This US attitude shows the collapse of the universalism of Western civilization, which has sacrificed democracy on a pragmatic political stage.